Ocean Acidification and Sea Temperature Rise Affect the Queen Scallop Aequipecten opercularis (Linnaeus, 1758) in Captivity - Ines Kovačić; Petra Burić; Neven Iveša; Anamarija Panić; Valentina Kolić; Ante Žunec; Jadranka Frece; Mauro Štifanić (Applied Sciences, 2024)
Climate change poses risks to bivalves; thus, searching for resilient alternative species is crucial for sustainable fisheries. This study examines the impact of reduced pH and elevated temperature and their combined effects on the queen scallop Aequipecten opercularis in captivity. The results indicated that a low pH reduced its growth rates in both weight (0.03 ± 0.05 g/day) and length (0.06 ± 0.16 mm/day), as well as leading to decreases in meat yield (20.75 ± 2.75%) and the condition index (44.21 ± 7.19%). Conversely, elevated temperature resulted in an increased growth in length (0.07 ± 0.23 g/day), meat yield (21.57 ± 4.82%), and condition index (45.42 ± 7.35%). Combined stressors initially promoted growth but ultimately produced unsustainable outcomes, resulting in a reduced meat yield (18.28 ± 2.60%) and condition index (38.92 ± 8.23%), along with a peak mortality rate of 27%. These findings indicate that while A. opercularis can withstand individual stressors, exposure to simultaneous stressors may compromise its long-term viability in aquaculture systems.